Osteogenic differentiation of human amniotic mesenchymal stem cells in chitosan-carbonate apatite scaffold (in vivo study) - Michael Josef Kridanto Kamadjaja; Sherman Salim; Fedik Abdul Rantam; Ni Putu Mira Sumarta (Wolters Kluwer Medknow Publications, 2018)
Background: Studies of bone tissue engineering as a viable alternative to autogenous bone graft show promising results, although its mechanism and effectiveness remain only partially understood. Purpose: to explain the osteogenic differentiation of scaffold chitosan (Ch)-carbonate apatite (CA) in seeding with human amniotic mesenchymal stem cells (hAMSCs) on the regeneration of calvarial bone defects in rats. Materials and Methods: Shitosan-Carbonate Apatite (Ch-CA) scaffold was created by means of a freeze-drying method. Twenty Wistar rats were randomly divided into two groups: control and treatment. Defects were created in the calvarial bone of each treatment group with a scaffold subsequently implanted. After 8 weeks, the rats were terminated for histology and immunohistochemistry examination. Results: Expressions of vascular endothelial growth factor, bone morphogenetic protein2, Runt-related transcription factor 2 (RUNX2), and angiogenesis occurred earlier in the tissue-engineered group than that in the control group. An 8-week analysis also showed that the expression of RUNX2, alkaline phosphatase, osteocalcin, and collagen type 1 was at more elevated levels in the treatment group than that in the control group. Conclusion: These results showed that the combination of hAMSCs and Ch-CA scaffold may become one of the candidates for bone tissue engineering.